Antecedentes da lealdade do estudante no ensino superior: uma generalização por meio de abordagem meta-analítica - Rocha, Luciana da Silva (Universidade do Vale do Rio dos Sinos, 2024)
This study synthesized and integrated findings from diverse research on the antecedents and moderators of student loyalty in higher education sector. Through a comprehensive meta-analysis, the research seeks to understand the primary drivers of student loyalty and the potential cultural and contextual indicators that might influence these relationships. This meta-analysis analyzed 106 studies involving over 54,000 students from more than 60 countries in all continents. The study identified key antecedents of student loyalty. Satisfaction was the most loyalty former influence following by student engagement and perceived value. We also detected significant cultural and contextual moderators. This research offers a holistic view of student loyalty, bridging gaps from conflicting findings in prior literature.
Keywords: Lealdade; Consumidor; Meta-análise; Instituição de ensino superior; Loyalty; Student; Teaching; Meta-analysis; Higher educations; ACCNPQ::Ciências Sociais Aplicadas::Administração